Potential methanogenic mixtures of substrates from agricultural - Zamojska-Jaroszewicz, Anna; Matuszewska, Anna; Owczuk, Marlena; Wardzińska, Dorota (Studia Ecologiae et Bioethicae, 2013)
The paper presents the results of research into the influence of organic fraction composition on yield and dynamics of anaerobic digestion of swine manure and silage maize mixtures. It defines the biological methane potential of individual mixtures and proposes the best option for biogas production on a larger scale.